The Second Usborne Book of SpineChillers - Cox, Phil Roxbee (Usborne Publishing Ltd, 1995)
Spooky stories filled with devious clues keep the reader guessing-- Thrilling mysteries unravel as each tale unfolds.
Keywords: Horror & Ghost Stories; Juvenile Fiction